Analysis of Feeder Needs to Support the Implementation of LRT in Palembang - Arliansyah, Joni (Unijourn Publisher, 2019)
Palembang City in August 2018 was the first city in Indonesia which operated a mass transit of Light Rail Transit (LRT). LRT in Palembang City has a length of 23 km and 13 stations that stretch from the Airport station to the DJKA station. In its first year of operation, it was noted that the number of passengers using LRT was still very small, some efforts were needed to increase the number of LRT passengers. This study aimed to increase the number of LRT passengers by analyzing the development of the feeder line, the potential for increasing the number of passengers, and the infrastructure needs to support LRT operations in Palembang. The results show that four stations have the potential to develop feeder lanes, namely Asrama Haji station, RSUD station, Garuda Dempo station, and Polresta station, with the increased total number of potential passengers of 1460 passengers/day. The supporting infrastructure needed to support movement using LRT consists of a park and ride facilities, pedestrian bridges, the construction and repair of pedestrian facilities, and drop-off and pick-up facilities.